The impact of a Customs Union with the EU on internal migration in Turkey under the two alternative Harris-Todaro and wage curve settings - Roberto A. De Santis (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1998)
The impact on internal migration of the recent Customs Union (CU) agreement between Turkey and the European Union (EU) has been studied with an intra-industry trade Applied General Equilibrium (AGE) model with intersectoral capital mobility, under two alternative specifications for the labour market: the traditional Harris- Todaro approach and the existence of a 'wage curve' in the urban sector. The numerical results show that, under both specifications, the CU leads to migration from rural to urban areas, despite agriculture remaining protected; causes a reduction of the urban unemployment rate and the urban-rural wage gap as suggested by theoretical studies; whilst raises the capital rent, a counter intuitive result with respect to the dual economy literature. Both scenarios suggest that internal migration is economically desirable, as it would contribute to a large rise in welfare. The study also shows that the proposal of uniformly subsidising the entire labour market maximises welfare, but the possibility that the high wage union sector can cream off more rents, and the large amount of financial resources required, make this policy unfeasible. It might be thought that the results of this kind of exercise would be highly sensitive to the assumptions made about the labour market. One of the contributions of this paper is to demonstrate that that is not the case.
Keywords: D58; F14; F15; F17; R23; 330; Customs Union; Internal Migration; AGE analysis; Turkey; Binnenwanderung; Lohnstruktur; Städtische Arbeitslosigkeit; Industriegüteraußenhandel; Allgemeines Gleichgewicht; Schätzung; Türkei; Theorie